Questioning as a Teaching Tool. The Media Systems Series in Creative Teaching - Thompson, Carolyn; Kentucky Univ., Lexington. Coll. of Allied Health Professions; Media Systems Corp., New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This two-part learning module was designed to help instructors in making effective use of questioning techniques in promoting the classroom involvement of non-traditional students. Part I identifies the characteristics and uses of three different types of questions: (1) convergent, eliciting questions, which are designed to verify student retention of factual information; (2) divergent, eliciting questions, which are designed to allow a variety of answers and which require the student to defend a position or develop a hypothesis; and (3) probing questions, which are designed to follow up on initial student responses by probing for the correct answer or seeking an extension, clarification, or justification of a student's response. Included in this section is a discussion of the relative merits of three intellectual levels of questioning: the knowledge level, which requires the student to rely upon memory for recalling facts; the application level, which requires the student to apply previously learned information to specific examples; and the problem-solving level, which requires the student to develop appropriate alternatives to new situations. Part II presents a series of exercises to help instructors apply the concepts of questioning techniques to the construction of questions for classroom use. A pre-test and several post-tests are provided. (JP)
Sponsoring Agency: Kellogg Foundation, Battle Creek, MI.
ERIC Note: Prepared for the Media Systems Series in Creative Teaching.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Creative Teaching; Learning Modules; Learning Theories; Lesson Plans; Nontraditional Students; Questioning Techniques; Teacher Education; Teacher Effectiveness; Teacher Improvement; Teaching Methods; Two Year Colleges; Blooms Taxonomy; Guides, Classroom -- Learner; Tests/Questionnaires.